2015
DOI: 10.1210/en.2014-1866
|View full text |Cite
|
Sign up to set email alerts
|

Calpain-10 Activity Underlies Angiotensin II-Induced Aldosterone Production in an Adrenal Glomerulosa Cell Model

Abstract: Aldosterone is a steroid hormone important in the regulation of blood pressure. Aberrant production of aldosterone results in the development and progression of diseases including hypertension and congestive heart failure; therefore, a complete understanding of aldosterone production is important for developing more effective treatments. Angiotensin II (AngII) regulates steroidogenesis, in part through its ability to increase intracellular calcium levels. Calcium can activate calpains, proteases classified as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…Calpain 10, a member of the calpain family, is a ubiquitously expressed mitochondrial and cytosolic Ca2+-regulated cysteine protease, researches have demonstrated that overexpression of Calpain 10 leads to mitochondrial dysfunction and cell death 29. Other research showed that Angiotensin II (AngII) induced activation of Calpain 10 24. Meanwhile previous studies have found significant increase of renal Angiotensin II (AngII) in DN 30,31.…”
Section: Discussionmentioning
confidence: 99%
“…Calpain 10, a member of the calpain family, is a ubiquitously expressed mitochondrial and cytosolic Ca2+-regulated cysteine protease, researches have demonstrated that overexpression of Calpain 10 leads to mitochondrial dysfunction and cell death 29. Other research showed that Angiotensin II (AngII) induced activation of Calpain 10 24. Meanwhile previous studies have found significant increase of renal Angiotensin II (AngII) in DN 30,31.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, calpastatin inhibits selectively calpains and no other proteases to date. Calpain activation has been linked recently to renal injury in several pathological contexts 69,70 . The calcium channel transporter Transient receptor potential channel C6 (TRPC6) was found to activate calpain-1 in podocyte via a Ca2+/calcineurin activation.…”
Section: Hsdmentioning
confidence: 99%